Clinical experience of combined organ-preserving treatment of laryngopharyngeal cancer with spread to the cervical esophagus - V. A. Rozhnov; P. I. Spirin; V. V. Polkin; I. А. Gulidov; A. V. Dem’yanovich; A. D. Kaprin; S. A. Ivanov (Опухоли головы и шеи, 2023)
Introduction. Laryngopharyngeal cancer accounts for about half of the total number of malignant neoplasms of ENT organs. Despite the availability of examination, in most patients tumors of this localization are detected at late stages, and the long-term results of treatment of locally advanced cancer of the larynx remain unsatisfactory.Clinical case. This article presents two clinical cases of combined organ-preserving treatment of laryngopharyngeal cancer with spread to the cervical esophagus. At the first stage, patients underwent organ-preserving surgical treatment with a reconstructive plastic component according to the methodology developed at the A.F. Tsyb Medical Radiological Research Center – branch of the National Medical Research Center of Radiology. Then a postoperative course of chemoradiotherapy was carried out.Conclusion. The use of combined organ-preserving techniques using displaced skin-muscle flaps in the treatment of locally advanced laryngopharyngeal cancer involving the cervical esophagus allows in some cases to avoid crippling surgery, preserve the larynx and achieve satisfactory functional results, which significantly improves the quality of life of patients.